Mapping global epidemiology of thyroid nodules among general population: A systematic review and meta-analysis - Mu, Chunyang; Ming, Xin; Tian, Ye; Liu, Yang; Yao, Menglin; Ni, Yinyun; Liu, Yong; Li, Zhihui (Frontiers in Oncology, 2022)
Introduction An emerging public health issue is brought on by the worldwide increase of thyroid nodules (TNs). The goal of the current study is to determine the global prevalence of TNs among the general population. Methods We screened articles published from January 2000 to May 2022. TN prevalence was calculated with the DerSimonian–Laird random effects model with arcsine transformation. Results A total of 20,358 entries were found in our research, and 102 of them met our inclusion criteria. A total of 9,276,178 individuals have been diagnosed as TNs; the overall prevalence was 24.83% (95% CI 21.44–28.55), regardless of the diagnostic techniques. TNs have become more prevalent during 2012–2022 (29.29%) compared with 2000–2011 (21.53%, p = 0.02). In addition, we discovered that women (36.51%) were more likely to have TNs than men (23.47%, p < 0.01). Interestingly, we found that obesity was correlated with the prevalence of TNs. Additionally, age-specific-stratified TN prevalence was found in our results. Discussion This meta-analysis shows that, regardless of country development and economic status, TNs are spreading more widely over the world. Our findings showed a strong correlation between rising TN prevalence and older age, female sex, and elevated weight. To stop the TN epidemic from spreading over the world, increased awareness, the understanding of the disease, and quick action are required.